Lake and reservoir management - Jorgensen S E; Loffleer H; Rast W; Straskraba M (Amsterdam Elsevier, 2005)
This book not only presents good lake management strategy but also explains the strategy by the use of limnology, chemistry, biochemistry - using all scientific disciplines needed to understand lake problems, lake processes and the tools that can be appl
Keywords: Hydraulic engineering; Lakes; Reservoirs